A Review Study on the Brand Image on the Customer’s Perspective - MEHRA, AASHISH; JAIN, VIPIN (The journal of contemporary issues in business and government, 2021)
The study paper reflects on the effect of branding on customer behavior. Brand awareness is a significant consideration here. As the customer is more knowledgeable of a brand but has all the awareness from its price, cost, etc., the further they would be drawn to the brand. The stage of loyalty rises with age. Community is by far the most prominent reference population in the world. Consumers who may be more interactive are influenced by their peers through social media platforms. Consumers who may be more mindful of their position are more apparent over those who haven’t conscious of their status. The brand name on customer buying behavior is at the demonstration in buying for products and services. Consumers are impacted by various social, emotional, cultural and behavioral circumstances. The study deals with the findings of the study, the aim of that was to consider the effect of branded product mostly on the influence of customers in buying a product. The goal of the study is to think about the very reality that perhaps a brand does have an impact on the consumer’s decision-making method. Throughout the end, it was assumed that the label was affected by the customer’s actions in addition to the following contingent and response variables.